Numerical and experimental investigation of flue gases heat recovery via condensing heat exchanger - Macháčková, Adéla; Kocich, Radim; Bojko, Marian; Kunčická, Lenka; Polko, Krzysztof (International journal of heat and mass transfer, 2018)
•Original heat exchanger was designed and evaluated numerically and experimentally.•1D condensing heat exchanger model based on Colburn-Hougen model was presented.•3D model on the basis of the 1D model was proposed and experimentally verified.•Proposed 3D model can be applied for heat recovery from coal-fired power plants. The ever increasing environmental awareness introduces the trend of increasing the efficiency of power plants via implementing waste heat recovery. This study reports two numerical models suitable for analyses of a condensing heat exchanger. The numerically predicted results are compared with the results acquired experimentally with the use of a coal-fired water condensing heat exchanger installed in the local laboratory of thermal engineering. The first applied mathematical model is a stationary 1D model based on our own modification of the Colburn-Hougen model. The second one is a proposed 3D multiphase flow model based on the Euler model of mixture expanded by the model of condensation of water vapour from the flue gases. A thorough comparative analysis of the results of both the numerical models and the experimental ones showed very good correlation. The differences between all the acquired results for the temperatures of flue gases and heated water at the outlet of the heat exchanger did not exceed 4 °C. In cases of heat recovery with the occurrence of condensation, the latent heat has a significant influence on the flue gases and water temperatures at heat exchanger outlet.